First Record of Free-Living Nematode Mylonchulus hawaiiensis from Bondowoso Regency-Indonesia - Ankardiansyah Pandu Pradana; Toyoshi Yoshiga (Jurnal Sumberdaya Hayati, 2023)
Monochids are predatory nematodes that can be found in various ecosystems. In this study, we analyzed monochids from the rhizosphere of Arabica coffee in Bondowoso Regency-Indonesia. The morphological analysis showed that the nematode belonged to the Mylonchulus hawaiiensis (Cassidy, 1931) species. The analysis results were also confirmed by a molecular analysis using DNA from a single nematode. The study also involved a polymerase chain reaction process using a forward primer SSU F07 (5’-AAA GAT TAA GCC ATG CAT G-3’) and reverse primer SSU R 81 (5’-TGA TCC WKC YGC AGG TTC AC-3’), which amplifies the small subunit (SSU) region of rDNA. Phylogenetic analysis of the sequence obtained formed a cluster with those of M. hawaiiensis found in GenBank. The sequences obtained had homology ranging from 99.64 to 99.70% compared with M. hawaiiensis sequences found in GenBank. This study is the first report of M. hawaiiensis from Indonesia.